TEKRONE COMPOSITE DUMPS ARE AN ALTERNATIVE FOR MODERN AGRICULTURAL MACHINERY - Yurchenko, O. Yu.; Kolodnenko, V. M. (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes, 2022)
Plowing, as one of the types of tillage, aims to meet a number of requirements to ensure the quality of the technological operation and perform its basic functions. Among the tasks set before this operation are: compliance with the specified depth of cultivation and not exceeding the allowable deviation, the formation of the layer should be dense, the cultivated layer of soil should be loose, all available weeds and crop residues should be completely plowed, etc. n. Achieving all the goals is possible only with high-quality selection of units to perform technological operations on certain areas of soil, as well as the choice of working bodies that are variable for agricultural machinery. When considering the plow as a unit for the main tillage, it should be noted that the structural parts of the body, such as dumps, plowshares, field boards, racks have a significant impact on the quality of the process. For example, changing the shape of the dump can significantly affect the process of overturning the treated layer, as well as the prioritization of weeds and crop residues. Increasing the efficiency and reducing the energy consumption of plowing is possible by solving problems to optimize such parameters of the plow as the width of the grip, the geometry and shape of the ploughshare surface of the body. Replacing body or their dumps is a rather long and laborious process, so its implementation, depending on production and meteorological situations, which are often variable, is extremely difficult. However, the time spent on operations to optimize the process of operation of the unit, namely - the replacement of its working bodies with more energy-efficient, durable and able to improve the quality of the technological operation, is justified by the result. This paper presents an analysis of the operation of Tekrone composite dumps, which were installed on a classic plow in order to optimize the operation of the machine-tractor unit. Since this operation does not change the design of the plow, the replacement of the dumps does not require additional intervention to other structural elements. The result of optimizing the plow is to reduce fuel consumption for the plowing process, reduce engine load, the ability to work in higher gear and increase the speed of tillage. At the same time, a significant advantage of composite dumps in comparison with iron ones was revealed – non-sticking of the working surface of the dump when working on wet soils, their quick cleaning, absence of corrosion processes and improved sliding of the treated soil layer on the dump surface. As a result, it can be concluded that Tekrone composite dumps can be an alternative to improve the quality of the plowing process.